"I'm sorry, my English not very good": Tracking differences between Language-Barrier and Non-Language-Barrier emergency ambulance calls for Out-of-Hospital Cardiac Arrest. (December 2021) - Perera, Nirukshi; Birnie, Tanya; Ngo, Hanh; Ball, Stephen; Whiteside, Austin; Bray, Janet; Bailey, Paul; Finn, Judith
Abstract: Background: One-fifth of Australia's population do not speak English at home. International studies have found emergency calls with language barriers (LB) result in longer delays to out-of-hospital cardiac arrest (OHCA) recognition, and lower rates of bystander cardiopulmonary resuscitation (CPR) and survival. This study compared LB and non-LB OHCA call time intervals in an Australian emergency medical service (EMS). Methods: The retrospective cohort study measured time intervals from call commencement for primary outcomes: (1) address acquisition; (2) OHCA recognition; (3) CPR initiation; (4) telecommunicator CPR (t-CPR) compressions, in all identified LB calls and a 2:1 random sample of non-LB EMS calls from January to June 2019. Results for time intervals #1, 2, and 4 were benchmarked against the American Heart Association's (AHA) t-CPR minimal acceptable time standards. Patient survival outcomes were compared. Results: We identified 50 (14%) LB calls from a cohort of 353 calls. LB calls took longer than non-LB calls (n=100) for: address acquisition (median 29 vs 14 secs, p<0.001), OHCA recognition (103 vs 85 secs, p=0.02), and CPR initiation (206 vs 164 secs, p=0.01), but not for t-CPR compressions (292 vs 248 secs, p=0.12). Rates of OHCA recognition and 30-day-survival did not differ but smaller proportions of LB calls met the AHA standards. Conclusion: Time delays found in LB calls point to phases of the call which need further qualitative investigation to understand how to improve communication. Overall, training call-takers for LB calls may assist caller understanding and cooperation during OHCAs.